2012
DOI: 10.1258/td.2012.120081
|View full text |Cite
|
Sign up to set email alerts
|

American Society for Gastrointestinal Endoscopy guidelines for appropriate use of colonoscopy: are they suitable for African patients?

Abstract: This study investigates the appropriateness and diagnostic yield of colonoscopy referrals in an African setting using the American Society of Gastrointestinal Endoscopy guidelines: a prospective, descriptive, cross-sectional hospital-based study. A total of 311 patients were included in the study; 228 referrals (73.3%) were considered appropriate and clinically significant pathology was found in 157 patients, giving an overall diagnostic yield of 50.5%. Diagnostic yield in those with appropriate referrals was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Appropriateness and diagnostic yield of colonoscopy referrals in an Africa was studied in Sudan and they found that part of the symptomatic patients (per rectal bleeding) have polyps. This study found that 50% of polyps presented with rectal bleeding [6].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Appropriateness and diagnostic yield of colonoscopy referrals in an Africa was studied in Sudan and they found that part of the symptomatic patients (per rectal bleeding) have polyps. This study found that 50% of polyps presented with rectal bleeding [6].…”
Section: Discussionmentioning
confidence: 59%
“…Lower GI endoscopies in form of colonoscopy and flexible sigmoidoscopy for symptomatic patiets was the gold standard method for diagnosis [6]. In our study Narrow band imaging (NBI) was used in 7.5% (n=9) and in these patients the type of polyps was found to be invasive carcinoma 2.5% (n=3), carcinoma in situ 0.8% (n=1) and high dysplasia 10.8% (n=13).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Diverticular disease (DD) was thought to be more prevalent in the western world especially the white populations, but the recent increase in incidence among the immigrants from Africa who reside in the west for more than ten years may indicate that the westernization of the lifestyle could be the cause for this change in DD epidemiology [ 1 , 23 , 24 ]. In Africa, the Middle East and Asia the prevalence is less [ 14 - 18 , 25 - 27 ]. In this study the prevalence of DD was 7.5% (104/1393) among all patients who underwent a colonoscopy to investigate gastro-intestinal symptoms which is comparable to a prevalence of 7.4% that reported previously in Saudi Arabia [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of males in our study is 77.1% and females were 22.9% which is consistent with previous studies from Africa, the USA and Europe [ 16 , 19 , 27 ]. Risk factors for colonic diverticulosis include: low fibre diet, increased age, smoking, obesity, lack of exercise and certain medications (NSAIDs, anticoagulants and corticosteroid) [ 1 , 15 , 19 , 25 , 27 , 28 ]. Sixty one patients were found to have one or more medical comorbidity in this study.…”
Section: Discussionmentioning
confidence: 99%